Polylactic acid plasticizer and polylactic acid film preparation process

CN121005952BActive Publication Date: 2026-10-16JIANGSU XINSHIJI NEW MATERIAL TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511118345.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-08-11
Publication Date
2026-10-16
Estimated Expiration
2045-08-11

AI Technical Summary

Technical Problem

[0005]本发明旨在克服现有PLA增塑剂生物基来源不足、相容性差、制备效率低,以及PLA薄膜力学性能与降解性难以平衡的问题,提供一种腰果酚-二聚酸基复合增塑剂及其制备方法,同时提供一种高性能聚乳酸薄膜的制备工艺

Benefits of technology

1、本发明中方案中,生物基来源增塑剂性能优异,原料为天然酚类的腰果酚和脂肪酸二聚物,100%生物基可完全降解契合环保需求;同时分子结构含酯基、醚键等,与PLA的酯键结构相似,具备较高的相容性,经等离子体处理引入极性基团,显著提升与PLA的界面结合力。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121005952B_ABST
    Figure CN121005952B_ABST
Patent Text Reader

Abstract

The application discloses a kind of polylactic acid plasticizer and polylactic acid film preparation process, belong to biomass conversion material field.Bio-based plasticizer with cashew phenol and (Z,Z)-9,12-octadecene acid dimer as raw material, by chlorohydrination, epoxy group reconstruction, etherification and other steps are prepared, preferably acidic molecular sieve and KOH / ZSM-5 are catalyst, optimization feed ratio and reaction condition, yield is higher;In the preparation of polylactic acid film, by oxygen plasma modification plasticizer, pre-mixed to form swelling layer, ultrasonic dispersion and bio-based compatibilizer control, significantly improve the compatibility of plasticizer and polylactic acid, the tensile strength, elongation at break, water absorption rate, degradation rate of the obtained film are at a higher level, with excellent mechanical properties, water resistance and biodegradability, suitable for packaging, medical and other fields.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a polylactic acid plasticizer and a polylactic acid film preparation process, belonging to the field of biomass conversion materials. Background Technology

[0002] Polylactic acid (PLA), as a biodegradable polymer, possesses excellent mechanical properties and biocompatibility, making it promising for applications in packaging, medicine, and other fields. However, the rigidity and high crystallinity of PLA molecular chains lead to high brittleness, low elongation at break, and poor processability, limiting its practical applications. To improve the flexibility and processability of PLA, plasticizers need to be added to reduce intermolecular forces and enhance chain segment mobility.

[0003] Existing PLA plasticizers are mostly petroleum-based compounds such as phthalates, which have problems such as poor biocompatibility and non-degradability, contradicting the environmentally friendly characteristics of PLA. Although bio-based plasticizers such as citrate esters and glycerol derivatives are degradable, they lack compatibility with PLA and are prone to migration, leading to a decline in the mechanical properties of the material over time. At the same time, the low catalyst efficiency and numerous side reactions in traditional plasticizer preparation processes further limit their application.

[0004] Furthermore, during PLA film preparation, issues such as poor interfacial compatibility and uneven dispersion between the plasticizer and the matrix can lead to fluctuations in the film's mechanical properties and a decrease in its water resistance. Therefore, developing a bio-based, highly compatible, and efficiently prepared plasticizer, along with a corresponding high-performance PLA film preparation process, is crucial to solving these problems. Summary of the Invention

[0005] This invention aims to overcome the problems of insufficient bio-based sources, poor compatibility, low preparation efficiency, and difficulty in balancing the mechanical properties and degradability of PLA films in existing PLA plasticizers. It provides a cashew phenol-dimer acid-based composite plasticizer and its preparation method, and also provides a preparation process for high-performance polylactic acid films.

[0006] The objective of this invention is achieved through the following technical solution: a polylactic acid plasticizer preparation process, comprising a bio-based plasticizer, wherein the bio-based plasticizer is a cashew nut phenol-dimer acid-based composite plasticizer, the main raw material is composed of cashew nut phenol and C36 dimer acid, and the auxiliary materials are composed of epichlorohydrin, solid acid catalyst, NaOH, and solid base catalyst; The preparation of the plasticizer includes the following steps: S1: C36 dimer acid is reacted with epichlorohydrin under the catalysis of a solid acid catalyst to generate a chlorohydrin intermediate; S2: After cooling, NaOH solution is added to the reaction system to carry out the elimination-cyclization process to rebuild the epoxy group, and the intermediate crude product of formula II is obtained by the reaction. S3: The intermediate crude product of Formula II is filtered to remove salt, and the reaction system is adjusted to neutral to remove water and unreacted epichlorohydrin to obtain Formula II. S4: The cashew phenol compound of formula II is etherified with cashew phenol under the catalysis of a solid base catalyst. After removing trace amounts of catalyst and byproducts, the cashew phenol-dimer acid group composite plasticizer, namely the compound of formula I, is obtained.

[0007] Preferably, the solid acid catalyst is at least one of acidic molecular sieve, AlCl3 / SiO2, FeCl3 / montmorillonite, strong acidic cation exchange resin, and hydrochloric acid modified raptosite, and the feed ratio of the solid acid catalyst to the C36 dimer acid is 0.04:1.

[0008] Furthermore, the product yield of solid acid catalysts using acidic molecular sieves is higher than that of AlCl3 / SiO2, FeCl3 / montmorillonite, strong acidic cation exchange resin, and hydrochloric acid modified attapulgite.

[0009] Furthermore, the acidic sites of acidic molecular sieves (such as zeolite molecular sieves) are mainly composed of moderately strong Brønsted and Lewis acids. The moderate acidity can effectively reduce the ring-opening energy barrier, activate epoxy groups, and promote the reaction. At the same time, it can avoid excessive ring-opening, self-polymerization, or decomposition of dimeric acids caused by excessive acidity, which would generate non-target byproducts and reduce the yield of intermediates. Meanwhile, acidic molecular sieves have uniform microporous and mesoporous structures. The channels of the molecular sieve can limit the excessive aggregation of large dimeric acids and allow small molecule epichlorohydrin to accumulate in the channels, increasing the local contact concentration of the two and accelerating the target reaction.

[0010] Preferably, the solid base catalyst is at least one of KOH / ZSM-5, magnesium oxide, calcium oxide, or NaOH solution-modified soapstone, and the feed ratio of the solid base catalyst to the C36 dimer acid is 0.04:1.

[0011] Furthermore, the product yield using KOH / ZSM-5 as a solid base catalyst is higher than that of magnesium oxide, calcium oxide, and NaOH solution-modified soapstone.

[0012] Furthermore, ZSM-5 molecular sieves possess a uniform microporous structure and a large specific surface area. These regular channels exhibit a "shape-selective catalysis" effect on the reaction of cashew phenol with compound II in step S4. The channels of ZSM-5 can restrict the disordered aggregation of the two, allowing them to contact the active sites in a specific orientation, thereby improving the effective collision efficiency between molecules. The generated cashew phenol-dimer acid group composite plasticizer can diffuse smoothly out of the channels, avoiding further side reactions such as epoxy ring-opening polymerization and phenolic hydroxyl oxidation within the pores. In contrast, magnesium oxide and calcium oxide have amorphous structures in the form of blocks or granules, without channel restrictions. Reactants and products diffuse freely, making them prone to side reactions such as self-polymerization of cashew phenol and excessive ring-opening of epoxy groups in compound II, leading to a decrease in yield.

[0013] Preferably, in step S1, the feeding ratio of the C36 dimer acid to the epichlorohydrin is 1:4~12, the temperature is raised to 110~115℃ after mixing, and the temperature is lowered to 90℃ after adding the solid acid catalyst.

[0014] Furthermore, the product yield was better when the feed ratio of C36 dimer acid to epichlorohydrin was 1:8.

[0015] Furthermore, the dimer is a long-chain fatty acid dimer with high viscosity; while epichlorohydrin acts as both a reactant and a solvent. When the feed ratio is 1:8, excess epichlorohydrin can effectively reduce the system viscosity, allowing the dimer and solid acid catalyst to be more uniformly dispersed, improving the contact efficiency between the reactants and the active sites of the catalyst, promoting mass transfer and reaction. Increasing the amount of epichlorohydrin can drive the reaction forward and improve the conversion rate of the dimer. When the feed ratio is less than 1:8, insufficient epichlorohydrin prevents the dimer from reacting fully, and the unreacted raw materials result in a reduced yield. If the ratio is too low, the system viscosity is too high, the catalyst is unevenly dispersed, and localized incomplete reactions further reduce the yield.

[0016] Furthermore, when the feed ratio exceeds 1:8, excessive epichlorohydrin may lead to self-polymerization or further reaction with the product, generating non-target byproducts, consuming raw materials and reducing the purity of the target intermediate. At the same time, step S3 requires the removal of unreacted epichlorohydrin, and excessive amounts will increase distillation energy consumption. Residual epichlorohydrin may interfere with the reaction in subsequent elimination-cyclization steps, resulting in a decrease in the final yield.

[0017] Preferably, in step S2, the amount of NaOH solution added is 2.4~4ep, the NaOH solution is selected as a 30% mass fraction solution, and the temperature during the addition is 45~55℃.

[0018] Furthermore, in this process, NaOH provides an alkaline environment to neutralize the HCl generated in the reaction and acts as a nucleophile to promote elimination-cyclization. When the amount of NaOH solution added is 2.8 eq, it can ensure the full progress of the elimination-cyclization reaction while avoiding side reactions caused by excess, thus achieving an optimal balance between reaction efficiency and product stability, resulting in a good yield.

[0019] Furthermore, using 2.8 eq of NaOH solution ensures that both active sites of the chlorohydrin intermediate react fully, avoiding raw material residue due to insufficient alkali, thereby improving the conversion rate. If the amount of NaOH is less than 2.8 eq, insufficient alkalinity will lead to incomplete elimination reaction, with some chlorohydrin intermediates not being converted into epoxy groups. The residual chlorohydrin structure will be washed away in subsequent processing or undergo other side reactions, directly reducing the yield. If the system is too alkaline, it will cause the generated Formula II compound to undergo non-selective ring opening, generating diol byproducts and destroying the target structure. Excessive NaOH may also react with unreacted epichlorohydrin in the system, initiating its hydrolysis or polymerization, consuming raw materials and generating impurities, increasing the difficulty of subsequent separation, and leading to a decrease in the final yield.

[0020] Preferably, in step S4, the reaction temperature is 110~125℃.

[0021] A process for preparing polylactic acid (PLA) film, wherein the main components of the PLA film are PLA particles and cashew phenol-dimer acid-based composite plasticizer, and the auxiliary materials are composed of bio-based compatibilizer, antioxidant 1010, multifunctional crosslinking agent, and organotin catalyst; The preparation of the polylactic acid film includes the following steps; T1: At 45℃, polylactic acid particles were placed in a DZF-200 vacuum drying oven and vacuum dried for 24 hours. T2: Oxygen plasma treatment of bio-based plasticizers, power 200W, time 5~10min, to introduce polar groups such as hydroxyl and carboxyl groups on their surface; T3: Premix the bio-based plasticizer with polylactic acid particles at 70~90℃, utilizing the fluidity of the bio-based plasticizer to penetrate into the interior of the polylactic acid particles and form a "swelling layer". Raise the temperature to 120~130℃, add the bio-based compatibilizer, and mix at a speed of 300~500rpm for 5~10min to ensure that the bio-based compatibilizer is evenly coated on the surface of the bio-based plasticizer and polylactic acid particles. Then raise the temperature to 145~150℃, increase the speed to 800~1000rpm, add the multifunctional crosslinking agent, organotin catalyst, and antioxidant 1010, and melt-blend for 15~20min. T4: Ultrasonic vibration is introduced during the melt blending process, with a power of 350~500W. The cavitation effect of ultrasound is used to break up the agglomerates of bio-based plasticizers and refine the size of the dispersed phase. T5: The compound is conveyed to the pressure molding machine for hot pressing at a temperature of 100℃~150℃ for 5 minutes. T6: Allow the sheet to cool naturally to room temperature, then cut a sample for testing.

[0022] Furthermore, the plasticizer penetrates into the polylactic acid particles to form a "swelling layer," expanding the interface for the compatibilizer's action.

[0023] Furthermore, acetylated lignin or starch-g-polylactic acid is uniformly coated onto the surface of PLA / plasticizer particles through high-speed shearing (300~500rpm), forming a stable interface layer.

[0024] Furthermore, ultrasonic vibration of 350~500W is introduced during the melt blending stage to break up plasticizer agglomerates using the cavitation effect, while promoting the extension and adsorption of compatibilizer molecular chains, thereby further refining the size of the dispersed phase.

[0025] Furthermore, the ester groups or grafted PLA segments of the compatibilizer can undergo a secondary reaction with the crosslinking agent (such as triethyl citrate) to form a "compatibility-crosslinking" synergistic network, which enhances mechanical properties while avoiding the increased brittleness caused by excessive crosslinking. Preferably, the bio-based compatibilizer is selected from at least one of lignin derivative and starch graft copolymer, wherein the lignin derivative is acetylated lignin and the starch graft copolymer is starch-g-polylactic acid.

[0026] Furthermore, the role of bio-based compatibilizers is to enhance the interfacial bonding between PLA and plasticizers through chemical bridging or physical entanglement, while avoiding the introduction of non-degradable petroleum-based components.

[0027] Furthermore, acetylated lignin is a natural phenolic polymer. The ester group of acetylated lignin has a similar ester bond structure to the PLA backbone. It forms chemical bonds with the PLA molecular chain through transesterification, which enhances the interfacial bonding. The benzene ring structure of lignin can serve as a physical crosslinking point, thereby improving the elastic modulus and tensile strength of the material.

[0028] Furthermore, starch is a hydrophilic polysaccharide. By grafting PLA segments (starch-g-polylactic acid), the hydrophilic hydroxyl groups are converted into hydrophobic PLA chains, achieving amphiphilic interface modification. The grafted PLA segments form physical entanglements with the PLA matrix, enhancing interfacial bonding. Starch particles are uniformly dispersed in the PLA matrix through the "bridging effect" of the PLA segments, inhibiting phase separation. Preferably, the multifunctional crosslinking agent is selected from at least one of diisocyanate and triethyl citrate, and the organotin catalyst is selected from dibutyltin dilaurate.

[0029] Furthermore, when triethyl citrate is used as a multifunctional crosslinking agent, the mechanical properties are better, but the water absorption and degradation rates are also superior.

[0030] Furthermore, triethyl citrate, as a bio-based ester compound, exhibits better compatibility with cashew phenol-dimer plasticizers and acetylated lignin. Through transesterification, it binds to the terminal hydroxyl and carboxyl groups of PLA molecular chains, allowing it to disperse uniformly in the system and form a moderately dense cross-linked network. This enhances the intermolecular forces, reduces molecular slippage under stress, and thus improves tensile strength and elastic modulus. Simultaneously, the flexible alkyl chain acts as a molecular buffer, allowing the molecular chains to stretch moderately under stress and preventing rigid breakage, resulting in a higher elongation at break. The ester bond cross-linked network it forms is more polar and has a moderate cross-linking density, making it easier for water molecules to penetrate, leading to a slightly higher water absorption rate. The ester bonds it forms are consistent with the PLA main chain structure, resulting in more stable cross-linking and a coordinated degradation rate, thus leading to relatively slow degradation.

[0031] Furthermore, the isocyanate groups of diisocyanates are highly reactive, readily reacting rapidly with trace amounts of water or hydroxyl groups in the system to form densely cross-linked regions, leading to stress concentration and reduced overall mechanical properties. Diisocyanates form urethane bonds through the reaction of -NCO with the hydroxyl groups of PLA. Their molecular structure contains hydrophobic methylene and aromatic ring structures, and the cross-linking density is higher. The hydrophobic structure reduces the polar interaction with water molecules, and the high-density cross-linking network can physically block the permeation channels of water molecules, thus resulting in a lower water absorption rate. The urethane bonds formed are more easily broken by esterases or hydrolases secreted by microorganisms than the ester bonds formed by triethyl citrate. The -NH- groups in the urethane bonds are easily recognized and attacked by enzymes, leading to faster disintegration of the cross-linking network. At the same time, the rigid micro-regions formed by the dense local cross-linking are more easily attached to by microorganisms in the early stages of degradation, accelerating the decomposition of the overall material, thus resulting in a higher degradation rate after 360 hours.

[0032] Preferably, the amount of bio-based plasticizer added is 15-25% of the amount of polylactic acid particles added.

[0033] In summary, compared with the prior art, the present invention has the following advantages: 1. In the present invention, the bio-based plasticizer has excellent performance. The raw materials are cashew nut phenol and fatty acid dimer, which are 100% bio-based and completely degradable, meeting environmental protection requirements. At the same time, the molecular structure contains ester groups, ether bonds, etc., which are similar to the ester bond structure of PLA and have high compatibility. The introduction of polar groups through plasma treatment significantly improves the interfacial bonding force with PLA.

[0034] 2. The PLA film prepared in this invention exhibits excellent overall performance. The synergistic effect of the plasticizer and compatibilizer results in outstanding mechanical properties, far exceeding those of pure PLA and traditional plasticizing systems. Performance can be controlled by selecting crosslinking agents. Triethyl citrate enhances mechanical properties, while diisocyanate optimizes water resistance and degradation, making it suitable for various application scenarios. Steps such as premixing the swelling layer and ultrasonic dispersion ensure uniform dispersion of the plasticizer, avoiding phase separation. The process is highly efficient and stable, with high stability in mass production.

[0035] 3. In the present invention, the entire process uses bio-based raw materials and recyclable catalysts, with no emissions of toxic or harmful substances. The film has a high degradation rate of 360 hours, achieving environmental protection throughout its entire life cycle of preparation, use, and degradation. Attached Figure Description

[0036] Figure 1 This is the synthetic route for compound I of the present invention; Figure 2 This is a flowchart illustrating the preparation process of the polylactic acid film of this invention. Detailed Implementation

[0037] The technical solution of the present invention will be further described in detail below through specific embodiments, but the present invention is not limited to these embodiments.

[0038] Example 1

[0039] C36 dimer acid (50.0 g, 0.089 mol) and epichlorohydrin (65.9 g, 0.71 mol, molar ratio 1:8) were added to a four-necked flask, stirred and slowly heated to 115 °C (heating rate 5 °C / min). 2 g of zeolite molecular sieve was added as a catalyst, and the temperature was maintained for 30 min to allow the catalyst to be fully dispersed. Then the temperature was lowered to 90 °C and the reaction was continued for 1.5 h. The acid value was monitored every 15 minutes to generate a chlorohydrin intermediate.

[0040] The reaction system temperature was lowered to 52℃, and 24.7g (2.8eq, 0.18mol) of NaOH solution (30%w / w) was slowly added dropwise through a constant pressure dropping funnel at a rate of 1-2 drops / second. During the addition, a water bath was used to maintain the temperature in the range of 50-55℃. After the addition was completed, the reaction was continued for 4 hours to obtain the intermediate crude product of compound II.

[0041] After the reaction was completed, the mixture was cooled to room temperature, and the reaction mixture was filtered. The filter cake was washed three times with 100 mL of toluene. The organic phases were combined and washed with 10% dilute hydrochloric acid solution until pH=6-7, and then washed with deionized water until neutral. The organic phase was transferred to a distillation flask, and excess epichlorohydrin was recovered by atmospheric distillation. Then, the mixture was distilled under reduced pressure (120℃ / 2 mmHg) to remove residual water and low-boiling substances, yielding a pale yellow compound of formula II (yield approximately 92%).

[0042] 27 g of cashew phenol and 30.0 g of the above-prepared compound of formula II were added to a four-necked flask, along with 3.2 g of KOH / ZSM-5 catalyst (10 wt%). The mixture was slowly heated to 120 °C (under nitrogen protection) and reacted at this temperature for 5 h. During this period, samples were taken every 1 h to monitor the formation of ether bonds using infrared spectroscopy. After the reaction was completed, the mixture was cooled to 60 °C, diluted with 50 mL of toluene, filtered to remove the solid catalyst, and the filtrate was washed three times with deionized water and once with saturated brine. The organic phase was dried with anhydrous sodium sulfate for 2 h, filtered, and then distilled under reduced pressure to remove toluene. Finally, the mixture was degassed at 130 °C / 0.5 mmHg for 30 min to obtain a light brown bio-based plasticizer (yield approximately 88%).

[0043] Example 2

[0044] Material preparation: PLA 100g, plasticizer 20g, acetylated lignin 5g, triethyl citrate 1g, dibutyltin dilaurate 0.1g, antioxidant 1010 0.2g Preparation steps: Polylactic acid granules were placed in a DZF-200 vacuum drying oven and dried for 24 hours at 45℃ and a vacuum degree ≤0.095MPa until the moisture content was reduced to ≤0.02%. The cashew phenol-dimer acid composite plasticizer was placed in a plasma treatment device, oxygen (purity ≥99.9%) was introduced, the power was set to 200W, and the treatment time was 5~10 minutes, introducing polar groups such as hydroxyl (-OH) and carboxyl (-COOH) groups onto the surface of the plasticizer.

[0045] The dried polylactic acid (PLA) granules and a surface-modified bio-based plasticizer are added to a high-speed mixer and mixed for 10 minutes at 70-90°C and 200-300 rpm to allow the plasticizer to penetrate into the PLA granules and form a "swollen layer". The temperature is then raised to 120-130°C, acetylated lignin is added, and the speed is increased to 300-500 rpm. Mixing is continued for 5-10 minutes to ensure the compatibilizer is evenly coated on the surface of the PLA / plasticizer granules. The temperature is further raised to 145-150°C, and the speed is increased to 800-1000 rpm. Triethyl citrate, dibutyltin dilaurate, and antioxidant 1010 are added sequentially, and the mixture is melt-blended for 15-20 minutes.

[0046] During the melt blending process, ultrasonic waves are introduced through an ultrasonic vibration device with a power of 350~500W, a frequency of 20~40kHz, and an action time of 10~15 minutes. The ultrasonic cavitation effect is used to break up plasticizer agglomerates and refine the size of the dispersed phase.

[0047] The mixed material is fed into a pressure molding machine and hot-pressed in a mold at 100~150℃ and 10~15MPa for 5 minutes to form a film of uniform thickness (mold parameters: length × width = 150mm × 150mm, thickness 0.1~0.5mm). The hot-pressed sheet is allowed to cool naturally to room temperature (23±2℃), and 100mm × 100mm samples are cut using a sample cutter and placed in a desiccator for later use.

[0048] Example 3

[0049] The polylactic acid film samples were subjected to tensile tests (refer to GB / T 1040.2-2022), water resistance tests, and degradation tests.

[0050] The mechanical properties of the polylactic acid film obtained in Example 2 were measured as follows: tensile strength (MPa) = 45.84; elongation at break (%) = 457.9; elastic modulus (MPa) = 1411.4.

[0051] The water resistance test data of the polylactic acid film obtained in Example 2 were as follows: 24-hour water absorption rate (%) = 0.324.

[0052] The degradation performance test data of the polylactic acid film obtained in Example 2 were as follows: 360-hour degradation rate (%) = 21.5.

[0053] Example 4

[0054] This example is a comparative example of Example 1. Following the steps of Example 1, the solid acid catalyst was replaced with AlCl3 / SiO2, FeCl3 / montmorillonite, strong acid cation exchange resin, hydrochloric acid modified attapulgite, etc., while other conditions remained unchanged. The yields were statistically analyzed, and the product yields were all <88%. Among them, the yield was the lowest ≤62% when using strong acid cation exchange resin.

[0055] Example 5

[0056] This example is a comparative example of Example 1. Following the steps of Example 1, the solid base catalyst was replaced with magnesium oxide, calcium oxide, or NaOH solution-modified soapstone, while other conditions remained unchanged. The yields were statistically analyzed, and the product yields were all <88%, with the lowest yield being ≤71.5% when calcium oxide was used.

[0057] Example 6

[0058] This example is a comparative example of Example 1. Following the steps of Example 1, the feed ratio of C36 dimer acid to epichlorohydrin was adjusted to 1:4, 1:5, 1:6, 1:7, 1:9, 1:10, 1:11, and 1:12, respectively, with other conditions remaining unchanged. The yield was statistically analyzed. When the feed ratio was 1:9, 1:10, and 1:11, the product yield was ≥88%, while the product yield was <88% when the feed ratio was 1:4, 1:5, 1:6, 1:7, and 1:12. Among these, the yield was the lowest at a feed ratio of 1:4, ≤66.5%.

[0059] Example 7

[0060] This example is a comparative example of Example 1. Following the steps of Example 1, the amount of NaOH solution added was adjusted to 2.4 eq, 2.5 eq, 3 eq, 3.5 eq, 3.8 eq, and 4 eq, respectively, with other conditions remaining unchanged. The yield was statistically analyzed. When the amount added was 2.4 eq and 2.5 eq, the product yield was ≤80%, and when the amount added was >3 eq, the product yield was 85%~90%. However, when the amount of NaOH solution added was >3 eq, a large amount of NaOH residue remained after the reaction. The neutralization step required the addition of more 10% dilute hydrochloric acid solution, which increased the difficulty of post-processing. At the same time, the production cost was not proportional to the increase in yield.

[0061] Example 8

[0062] This embodiment is a comparative example of Embodiment 2. Following the steps of Example 2, the multifunctional crosslinking agent was replaced with diisocyanate, while other conditions remained unchanged. The polylactic acid film samples were subjected to tensile tests (refer to GB / T 1040.2-2022), water resistance tests, and degradation tests.

[0063] The mechanical properties of the obtained polylactic acid film were as follows: tensile strength (MPa) = 42.13; elongation at break (%) = 380.1; elastic modulus (MPa) = 1127.0.

[0064] The water resistance test data of the obtained polylactic acid film is: 24-hour water absorption rate (%) = 0.215.

[0065] The degradation performance test data of the obtained polylactic acid film is as follows: 360-hour degradation rate (%) = 27.

[0066] Example 9

[0067] This example is a comparative example of Example 2. Following the steps of Example 2, the amount of bio-based plasticizer added was adjusted to 15g, 17.5g, 22.5g, and 25g, respectively, while other conditions remained unchanged; The product was tested, and when the amount of bio-based plasticizer added was <18%, the tensile strength (MPa) of the obtained polylactic acid film was ≤35, the elongation at break (%) was ≤330, the elastic modulus (MPa) was ≤1000, and the degradation rate (%) after 360 hours was ≤12. When the amount of bio-based plasticizer added is >20%, the product is tested and the tensile strength (MPa) of the obtained polylactic acid film is ≤38.1, the elongation at break (%) is ≤427, the elastic modulus (MPa) is ≤1000, the degradation rate (%) after 360 hours is ≤26.4, and the water absorption rate (%) after 24 hours is ≤0.397. The conclusion is that when the amount of bio-based plasticizer added is reduced, the mechanical properties of the polylactic acid film decrease, and the degradation rate also decreases. When the amount of bio-based plasticizer added is excessive, the tensile strength and elongation at break of the polylactic acid film are better, but the elastic modulus decreases, while the degradation rate at 360 hours and the water absorption rate at 24 hours are significantly improved.

[0068] The embodiments of the present invention are not limited to those described above. Without departing from the spirit and scope of the present invention, those skilled in the art can make various changes and improvements to the present invention in form and detail, and these are all considered to fall within the protection scope of the present invention.

Claims

1. A process for preparing a plasticizer for polylactic acid films, characterized in that: The plasticizer is a cashew nut phenol-dimer acid-based composite plasticizer. The main raw material is composed of cashew nut phenol and C36 dimer acid, and the auxiliary materials are composed of epichlorohydrin, solid acid catalyst, NaOH, and solid base catalyst. The solid acid catalyst is an acidic molecular sieve, and the solid base catalyst is KOH / ZSM-5. The preparation process of the plasticizer includes the following steps: S1: C36 dimer acid and epichlorohydrin are reacted under the catalysis of a solid acid catalyst to generate a chlorohydrin intermediate. The feed ratio of C36 dimer acid to epichlorohydrin is 1:

8. After mixing, the temperature is raised to 110~115℃. After adding the solid acid catalyst, the temperature is lowered to 90℃. The feed ratio of the solid acid catalyst to C36 dimer acid is 0.04:

1. S2: After cooling, NaOH solution is added to the reaction system to carry out the elimination-cyclization process to rebuild the epoxy group, and the intermediate crude product of compound II is obtained. The amount of NaOH solution added is 2.4~4ep, the NaOH solution is a 30% mass fraction solution, and the temperature during the addition is 45~55℃. S3: The intermediate crude product of Formula II is filtered to remove salt, and the reaction system is adjusted to neutral to remove water and unreacted epichlorohydrin to obtain Formula II. S4: The compound of formula II is reacted with cashew phenol under the catalysis of KOH / ZSM-5 at a reaction temperature of 110~125℃. After removing trace amounts of catalyst and byproducts, the cashew phenol-dimer acid-based composite plasticizer, namely the compound of formula I, is obtained. The feed ratio of the solid base catalyst to the C36 dimer acid is 0.04:

1. The structural formula of compound II is: ; The structural formula of compound I is: 。 2. A process for preparing polylactic acid films, characterized in that: The main component of the polylactic acid film is cashew phenol-dimer acid-based composite plasticizer prepared by the preparation process of polylactic acid particles and the plasticizer for preparing polylactic acid film according to claim 1. The excipients are composed of bio-based compatibilizer, antioxidant 1010, multifunctional crosslinking agent and organotin catalyst. The preparation process of the polylactic acid film includes the following steps; T1: At 45℃, polylactic acid particles were placed in a DZF-200 vacuum drying oven and vacuum dried for 24 hours. T2: The cashew phenol-dimer acid complex plasticizer is subjected to oxygen plasma treatment at a power of 200W for 5-10 minutes to introduce polar groups of hydroxyl and carboxyl groups on its surface. T3: Premix cashew phenol-dimer acid composite plasticizer with polylactic acid particles at 70~90℃. Utilize the fluidity of the cashew phenol-dimer acid composite plasticizer to penetrate into the interior of the polylactic acid particles to form a "swelling layer". Raise the temperature to 120~130℃, add a bio-based compatibilizer, and mix at a speed of 300~500 rpm for 5~10 minutes to ensure that the bio-based compatibilizer is evenly coated on the surface of the plasticizer and polylactic acid particles. Then raise the temperature to 145~150℃, increase the speed to 800~1000 rpm, add a multifunctional crosslinking agent, organotin catalyst, and antioxidant 1010, and melt-blend for 15~20 minutes. T4: Ultrasonic vibration is introduced during the melt blending process, with a power of 350~500W. The cavitation effect of ultrasound is used to break up the agglomerates of plasticizer and refine the size of the dispersed phase. T5: The compound is conveyed to the pressure molding machine for hot pressing at a temperature of 100℃~150℃ for 5 minutes. T6: Allow the sheet to cool naturally to room temperature, then cut a sample for testing.

3. The polylactic acid film preparation process according to claim 2, characterized in that: The bio-based compatibilizer is either acetylated lignin or starch-g-polylactic acid.

4. The polylactic acid film preparation process according to claim 2, characterized in that: The multifunctional crosslinking agent is either diisocyanate or triethyl citrate, and the organotin catalyst is dibutyltin dilaurate.

5. The polylactic acid film preparation process according to claim 2, characterized in that: The amount of plasticizer added is 15-25% of the amount of polylactic acid granules added.

Citation Information

Patent Citations

  • Synthetic method of glycidyl methacrylate

    CN104086509A

  • Natural monophenol grafted dimer acid diglycidyl ester plasticizer as well as preparation method and application thereof

    CN117024274A